N-Glycosylation and Inflammation; the Not-So-Sweet Relation - Radovani, Barbara; Gudelj, Ivan (Frontiers in Immunology, 2022)
Chronic inflammation is the main feature of many long-term inflammatory diseases such as autoimmune diseases, metabolic disorders, and cancer. There is a growing number of studies in which alterations of N-glycosylation have been observed in many pathophysiological conditions, yet studies of the underlying mechanisms that precede N-glycome changes are still sparse. Proinflammatory cytokines have been shown to alter the substrate synthesis pathways as well as the expression of glycosyltransferases required for the biosynthesis of N-glycans. The resulting N-glycosylation changes can further contribute to disease pathogenesis through modulation of various aspects of immune cell processes, including those relevant to pathogen recognition and fine-tuning the inflammatory response. This review summarizes our current knowledge of inflammation-induced N-glycosylation changes, with a particular focus on specific subsets of immune cells of innate and adaptive immunity and how these changes affect their effector functions, cell interactions, and signal transduction.